Embryo ecology: Developmental synchrony and asynchrony in the embryonic development of wild annual fish populations - Polačik, Matej; Vrtílek, Milan; Reichard, Martin; Žák, Jakub; Blažek, Radim; Podrabsky, Jason (Ecology and evolution, 2021)
Embryo-environment interactions are of paramount importance during the development of all organisms, and impacts during this period can echo far into later stages of ontogeny. African annual fish of the genus Nothobranchius live in temporary pools and their eggs survive the dry season in the dry bottom substrate of the pools by entering a facultative developmental arrest termed diapause. Uniquely among animals, the embryos (encased in eggs) may enter diapause at three different developmental stages. Such a system allows for the potential to employ different regulation mechanisms for each diapause. We sampled multiple Nothobranchius embryo banks across the progressing season, species, and populations. We present important baseline field data and examine the role of environmental regulation in the embryonic development of this unique system. We describe the course of embryo development in the wild and find it to be very different from the typical development under laboratory conditions. Development across the embryo banks was synchronized within and across the sampled populations with all embryos entering diapause I during the rainy season and diapause II during the dry season. Asynchrony occurred at transient phases of the habitat, during the process of habitat desiccation, and at the end of the dry season. Our findings reveal the significance of environmental conditions in the serial character of the annual fish diapauses.
Keywords: egg bank; phenotypic plasticity; facultative; dormancy; bet‐hedging